Pounding between adjacent buildings in consideration of soil structure interaction - Naserkhaki, Sadegh (2011)
Earthquake is known as one of the most devastating natural disasters to human and their environment that causes catastrophic failure of their life and belongings particularly buildings. The main cause of numerous building failures is collision of adjacent buildings during the earthquake which is called building pounding. It occurs when the separation gap between adjacent buildings is less than minimum distant required for them to vibrate freely. As consequence of building pounding, seismic responses of buildings are altered and in some occasions it produces larger forces and displacements than the design limits which causes building damage. The aim of this research project is to numerically investigate seismic responses of two adjacent buildings due to earthquake induced building pounding. As the buildings are usually constructed on the soil; interaction between building and soil and further interaction between two buildings through the soil are considered in this research project. Other parameters affecting building pounding such as separation gap, dynamic property of building and earthquake excitation are studied too. In order to achieve the aim of this research project, a new analytical model of building pounding considering soil effect is developed. The proposed model consists of two adjacent shear buildings connected with linear visco-elastic contact force model during pounding constructed on a homogenous half-space soil. This model is then implemented into a computer program and calibrated and validated. It is found that the proposed model is efficient and accurate to evaluate seismic responses of buildings with soil effect considerations due to building pounding. A comprehensive number of analyses are then performed and results are explained and interpreted graphically in terms of building displacement and story shear. When a tall and flexible building is pounded to an adjacent short and stiff building,displacements of tall and flexible building are reduced but displacements of short and stiff building are increased. Considering soil effect (structure-soil-structure interaction, SSSI), produced displacements in both buildings due to pounding are greater than fixed-based (FB) buildings. On the other hand, building pounding causes increment of story shears of both buildings and this increment is pronounced if SSSI condition is considered. In conclusion, building pounding worsens buildings conditions and underlying soil amplifies this detrimental effect. Further analyses are performed to clarify effects of separation gap, dynamic property of building and earthquake excitation in building pounding. Separation gap between two adjacent buildings is found to be very critical. Number of collisions and intensity of pounding forces are increased due to reduction of separation gap. Therefore, wider separation gap is necessary to prevent building pounding when the soil is considered,particularly if the soil is soft. In addition, evaluation of variation of buildings dynamic properties (building height) indicates more intense building pounding for tall and flexible building when the period ratio of the buildings is about half. While for short and stiff building, the most critical condition is referred to the least period ratio. Finally, the results show that each earthquake produces unique effect for different buildings and underlying soils. Thus seismic responses of adjacent buildings due to earthquake induced pounding should be analyzed in case by case basis and soil effects, particularly soft soils must be taken into consideration.